Motivasi Masyarakat Dalam Beraktivitas Olahraga Di Car Free Day Alun-Alun Kabupaten Demak (Universitas Negeri Semarang, 2021)
The purpose of this research to describe the community's motivation to sport activities In the Car Free Day Square of Demak district. The research method used Is a survey through a quantitative approach. Data collection Is done by observation, Interviews, and questionnaires. The results showed that the community's motivation to exercise due to physiological needs had a percentage of 24.28%, a safety requirement of 22.62%, a social need of 19.93%, the need for an award of 11.05%, and self-actualisation requirement of 22.12%. From the results of this Identification, the community Is expected to better balance all needs so as not to weigh In on one's needs to create better conditions. Then for the local government to expand the hygiene facilities such as trash cans and handwashing places and for organizers or community leaders still provide the best service so that the community Is Increasingly motivated to exercise In the Car Free Day of Demak District Square.